Agonists of TRAIL death receptors induce myeloma cell apoptosis that is not prevented by cells of the bone marrow microenvironment. - Locklin, R; Croucher, P; Russell, R; Edwards, C (2007)
The growth and survival of myeloma cells is critically regulated by cells of the bone marrow microenvironment, including osteoblasts. Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) is a potent inducer of myeloma cell apoptosis, however, this antimyeloma activity is inhibited by osteoprotegerin (OPG) released from osteoblasts. Therefore, we hypothesized that specific agonists of TRAIL death receptors would not be inhibited by OPG released from osteoblasts and thus may represent a novel therapeutic approach in multiple myeloma. In the present study, TRAIL-induced apoptosis was demonstrated to be mediated through both DR4 and DR5. Specific agonist antibodies to DR4 or DR5 dose-dependently induced myeloma cell apoptosis, which was not prevented by OPG or by medium conditioned by osteoblasts. Co-culture of myeloma cells with osteoblasts protected against TRAIL-induced apoptosis of myeloma cells, and this protective effect was due to OPG. In contrast, the co-culture of myeloma cells with osteoblasts had no protective effect on apoptosis induced by specific agonists of DR4 or DR5. TRAIL has been proposed as a potential antitumour therapy, but within the bone marrow microenvironment OPG may interfere with the action of TRAIL. Specific agonists of TRAIL death receptors would not be subject to this inhibition and thus may provide an alternative specific antimyeloma therapy.